2016
DOI: 10.1002/srin.201600292
|View full text |Cite
|
Sign up to set email alerts
|

An Ab Initio Study of Carbon-Induced Ordering in Austenitic Fe-Mn-Al-C Alloys

Abstract: Short-range ordering around carbon interstitials in face-centered cubic (fcc) Fe-Mn-Al is studied by density-functional theory, considering the configuration of Fe, Mn, Al atoms in the first three coordination spheres of a carbon atom in an octahedral site. The ordering energies are derived from the solution energies of carbon in different environments, and these energies show that carbon prefers manganese as a first-nearest neighbor while the impact of manganese as a second-or third-nearest neighbor is neglig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Second-nearest neighbors (2NN) in this model are the grey atoms on the corners of the FCC lattice. Although third-nearest neighbors (3NN) can be included in first-principle calculations, a recent study has shown that neither 3NN Al atoms nor 3NN Mn atoms have a positive impact o the ordering energy [33]. To reduce the complexity of the calculations and limit the amount of possible cell configurations, the presence of 3NN alloying atoms is not accounted for in the analysis carried out in this paper.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Second-nearest neighbors (2NN) in this model are the grey atoms on the corners of the FCC lattice. Although third-nearest neighbors (3NN) can be included in first-principle calculations, a recent study has shown that neither 3NN Al atoms nor 3NN Mn atoms have a positive impact o the ordering energy [33]. To reduce the complexity of the calculations and limit the amount of possible cell configurations, the presence of 3NN alloying atoms is not accounted for in the analysis carried out in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…Ab initio calculations show that Al is preferentially situated in the second coordination sphere and Mn has a positive effect on the ordering energy level if it sits on a lattice position as a 1NN [22,25,33]. According to those studies, this means that the difference in ordering energy is so profound that the likelihood of a cell configuration that contains 1NN Al atoms instead of 2NN Al atoms or 2NN Mn atoms instead of 1NN Mn atoms is very low.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations